Fatigue after initiating rivaroxaban for venous thromboembolism - Tina Margrethe Karlsvik; Thore Langfeldt Borgenvik; Mirjam Aadalen; Kristin Utne; Eli Førsund; Camilla Tøvik Jørgensen; René Holst; Lars‐Petter Jelsness‐Jørgensen; Waleed Ghanima (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract Background Rivaroxaban was the first new oral anticoagulant approved for treatment of venous thromboembolism (VTE). Clinical trials have shown that rivaroxaban is noninferior to conventional anticoagulation for VTE in efficacy and safety. Increased fatigue after the initiation of rivaroxaban has been observed in clinical practice, but data on this potential side effect are lacking. Objective The study aimed to evaluate development of fatigue in patients treated for VTE, comparing rivaroxaban to other anticoagulants. Methods Patients were prospectively recruited after a diagnosis of VTE. The Fatigue Questionnaire was used to determine the level of fatigue at baseline, at 3 weeks of treatment, and either at 1 month after the discontinuation of treatment if the treatment was discontinued after 3 months or at 6 months if treatment was continued beyond this time. Data was analyzed by a linear mixed model. Results A total of 126 patients were included. Mean age was 59 years; 77 (61%) were males. Fifty‐seven patients (45%) were diagnosed with deep vein thrombosis, 48 (38%) with pulmonary embolism, and 21 (17%) with both. Predicted changes in fatigue scores from baseline to the last measurement were −0.007 and −2.49 for the rivaroxaban and the other‐anticoagulants groups, respectively, neither of which were statistically significant. No difference was detected between rivaroxaban and the other‐anticoagulants group at any time point, including subgroup analysis comparing over and under 6 months of treatment duration. Conclusion In this small study, our results suggest no increase in the level of fatigue after the initiation of treatment with rivaroxaban for VTE.